Silicon clathrate electrode active material particles, electrode mixture, and lithium-ion battery

By employing silicon clathrate electrode active material particles with controlled surface oxidation and porosity, the expansion issue is mitigated, leading to improved lithium-ion battery stability and performance.

JP2025018615APending Publication Date: 2025-02-06TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023122484
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Silicon clathrate electrode active materials experience significant expansion during charging, which needs to be further suppressed to enhance the performance of lithium-ion batteries.

Method used

The use of silicon clathrate electrode active material particles with a specific surface oxygen percentage to specific surface area ratio of 0 < (wt%)/(m²/g) < 0.3, combined with a porous structure, to control oxidation and accommodate expansion, thereby stabilizing the material.

Benefits of technology

This approach results in lithium-ion batteries with reduced expansion during charging, maintaining structural integrity and improving battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018615000001
    Figure 2025018615000001
Patent Text Reader

Abstract

To provide electrode active material particles that have low expansion during charging and a lithium-ion battery having the same.SOLUTION: The silicon clathrate electrode active material particles satisfy the following relationship: 0<surface oxygen content (wt%) / specific surface area (m2 / g)<0.3. The electrode mixture includes the electrode active material particles. The lithium-ion battery has an electrode active material layer. The electrode active material layer contains the electrode mixture.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to silicon-class rate electrode active material particles, an electrode binder, and a lithium-ion battery.

Background Art

[0002] In recent years, battery development has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles has been promoted. Also, silicon is known as an electrode active material used in batteries, particularly lithium-ion batteries.

[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. On the other hand, silicon electrode active materials have a problem of large expansion during charging. In contrast, it is known that by using silicon-class rate electrode active materials as the silicon electrode active material, expansion during charging can be suppressed.

[0004] For example, Patent Document 1 discloses a silicon-class rate electrode active material having a silicon-class rate type II crystal phase and having a composition of Na x Si 136 (1.98 < x < 2.54).

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] Although silicon-class rate electrode active materials can suppress expansion during charging compared to ordinary silicon electrode active materials, it is required to further suppress the expansion of silicon-class rate electrode active materials during charging.

[0007] An object of the present disclosure is to provide electrode active material particles that undergo small expansion during charging, and a lithium ion battery having such electrode active material particles. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> Silicon clathrate electrode active material particles that satisfy the following relational formula: 0<Oxygen content on the surface (wt%) / specific surface area (m 2 / g)<0.3. <Aspect 2> Electrode active material particles according to embodiment 1, which satisfy the following relational formula: 0.05≦Oxygen ratio on surface (wt%) / specific surface area (m 2 / g)≦0.1. <Aspect 3> 3. The electrode active material particles according to claim 1 or 2, having a porous structure. <Aspect 4> The electrode active material particles according to any one of aspects 1 to 3 are included. Electrode composite material. <Aspect 5> An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to aspect 4. Lithium-ion battery. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide electrode active material particles that expand little during charging, and a lithium ion battery having such electrode active material particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] <Silicon clathrate electrode active material particles> The silicon clathrate electrode active material particles of the present disclosure satisfy the following relationship: 0<Oxygen content on the surface (wt%) / specific surface area (m 2 / g)<0.3.

[0012] If the surface of a silicon electrode active material particle is oxidized to become insulating silicon oxide, the conductivity of the silicon electrode active material particle decreases, and therefore it has been thought that it is preferable that the surface of the silicon electrode active material particle is as unoxidized as possible.

[0013] However, the present inventors have found that when the surface of silicon clathrate electrode active material particles is moderately oxidized, the fluctuation of the confining pressure is small when used in a battery. Without being bound by any theory, it is believed that this is because the following action and effect occurs when the surface of silicon electrode active material particles is moderately oxidized. That is, when used as a battery, silicon oxide on the surface of the silicon electrode active material particles reacts with lithium to become lithium silicate, which has superior ion conductivity compared to silicon oxide, making it possible to suppress uneven reaction between the silicon clathrate electrode active material particles and lithium, while the lithium silicate is thin and does not excessively hinder electronic conduction.

[0014] In the present disclosure, the "electrode active material" can be used as either a "positive electrode active material" or a "negative electrode active material", and is particularly used as a "negative electrode active material".

[0015] Surface oxygen ratio (wt%) / specific surface area (m 2 / g) may be 0.01 or more, 0.03 or more, 0.05 or more, 0.06 or more, or 0.07 or more, and may be 0.25 or less, 0.20 or less, 0.15 or less, or 0.10 or less.

[0016] The proportion of oxygen on the surface of the electrode active material particles may be more than 0 wt%, 0.5 wt% or more, 1.0 wt% or more, 1.5 wt% or more, 2.0 wt% or more, 2.5 wt% or more, 3.0 wt% or more, or 3.5 wt% or more, and may be 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 8.0 wt% or less, or 6.0 wt% or less.

[0017] The method for measuring the oxygen ratio on the surface of the electrode active material particles is not particularly limited, and examples thereof include elemental analysis using an oxygen / nitrogen / hydrogen analyzer, and calculation methods based on analytical values ​​obtained by SEM-EDX, XPS, AES, etc. For example, when an oxygen / nitrogen / hydrogen analyzer is used, the oxygen ratio can be calculated from the results of measurement using a non-dispersive infrared absorption method after melting with oxygen gas using an EMGA-930 manufactured by Horiba, Ltd.

[0018] The specific surface area of ​​the electrode active material particles is 15m 2 / g or more, 25m 2 / g or more, 35m 2 / g or more, 45m 2 / g or more, or 50m 2 / g or more, 2 / g or less, 90m 2 / g or less, 80m 2 / g or less, 75m 2 / g or less, or 70m 2 / g or less.

[0019] The method of calculating the specific surface area of ​​the electrode active material particles is not particularly limited, but may be exemplified by a method of calculating by the BET method.Specifically, the surface area measured by a low-volume adsorption method (nitrogen gas adsorption method) using nitrogen gas can be calculated by analyzing by the BET method.For example, BELSORP MAX II of MICROTRACBEL Co., Ltd. can be used for this analysis.

[0020] Examples of methods for producing the electrode active material particles of the present disclosure include, but are not limited to, a method including mixing a silicon raw material and a sodium source and heating to form an alloy, thereby obtaining a powdered sodium silicon (NaSi) alloy, and mixing the obtained NaSi alloy with aluminum fluoride and heating to form a clathrate, thereby obtaining a silicon clathrate.

[0021] The sodium source in the alloying step can be exemplified by, but is not limited to, sodium hydride.

[0022] The heating temperature in the alloying step may be 300° C. or more, 350° C. or more, or 380° C. or more, and may be 500° C. or less, 450° C. or less, or 420° C. or less. The heating time may be 20 hours or more, 30 hours or more, or 35 hours or more, and may be 60 hours or less, 50 hours or less, or 45 hours or less.

[0023] The heating temperature in the clathration step may be 250° C. or more, 280° C. or more, or 300° C. or more, and may be 400° C. or less, 380° C. or less, or 350° C. or less. The heating time may be 10 hours or more, 15 hours or more, or 20 hours or more, and may be 70 hours or less, 65 hours or less, or 60 hours or less.

[0024] The oxygen ratio and specific surface area on the surface of the silicon clathrate electrode active material particles can be controlled by adjusting the heating temperature and heating time in the alloying step and the heating temperature and heating time in the clathrate step.

[0025] Furthermore, the electrode active material particles may be washed with a hydrogen fluoride solution. In this way, the oxygen ratio and the specific surface area on the surface of the electrode active material particles can also be controlled by washing the electrode active material particles with a hydrogen fluoride solution.

[0026] The electrode active material particles of the present disclosure may have a porous structure. The porous silicon clathrate can absorb expansion due to charging and discharging by its voids.

[0027] Examples of methods for producing the electrode active material particles of the present disclosure in the case of porous silicon clathrate particles include, but are not limited to, a method comprising mixing silicon and metallic lithium to obtain a lithium silicon (LiSi) alloy, reacting the obtained LiSi alloy with ethanol to obtain porous silicon, and using the obtained porous silicon as a silicon raw material to obtain a silicon clathrate as described above.

[0028] In this way, by making the electrode active material particles have a porous structure, the specific surface area of ​​the electrode active material particles can also be controlled.

[0029] 《Electrode composite material》 The electrode mix of the present disclosure includes electrode active material particles. The electrode mix of the present disclosure optionally contains a solid electrolyte, a conductive additive, and a binder.

[0030] <Electrode active material particles> For the electrode active material particles, reference can be made to the above description regarding the electrode active material particles of the present disclosure.

[0031] <Solid electrolyte> The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.

[0032] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11, Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0033] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).

[0034] <Conductive assistant> The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0035] <binder> The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.

[0036] In the present disclosure, the term "electrode mixture" refers to a composition that can constitute an electrode active material layer as it is or by further containing other components. In the present disclosure, the term "electrode mixture slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode mixture" and can be applied and dried to form an electrode active material layer.

[0037] Lithium-ion battery The lithium ion battery of the present disclosure may be a liquid battery or a solid-state battery. In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.

[0038] The lithium ion battery of the present disclosure can be restrained from both sides of the stacking direction of each of the layers by restraining members such as end plates. Examples of the restraining method include, but are not limited to, a method that utilizes the restraining torque of a bolt.

[0039] The lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode mixture of the present disclosure. In particular, the lithium ion battery of the present disclosure may have a negative electrode mixture which is the electrode mixture of the present disclosure, and in this case, may include, in this order, a negative electrode current collector layer, a negative electrode active material layer containing the electrode mixture of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer.

[0040] <Negative electrode current collector layer> The material used for the negative electrode current collector layer is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, the material may be copper, a copper alloy, or copper plated or vapor-deposited with nickel, chromium, carbon, or the like, but is not limited to these.

[0041] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0042] <Negative electrode active material layer> The negative electrode active material layer contains the electrode mixture of the present disclosure. For the electrode mixture, reference can be made to the above description of the electrode mixture of the present disclosure.

[0043] When the negative electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the negative electrode active material layer (mass of electrode active material particles:mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.

[0044] The negative electrode active material layer may have a thickness of, for example, 0.1 to 1000 μm.

[0045] <Solid electrolyte layer> The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding the electrode mixture of the present disclosure can be referred to.

[0046] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, and preferably 0.1 to 100 μm.

[0047] <Cathode active material layer> The positive electrode active material layer is a layer containing a positive electrode active material, and optionally a solid electrolyte, a conductive assistant, a binder, a thickener, and the like.

[0048] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y Li-Mn spinel substituted with different elements, which has a composition represented by MyO4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), and lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co, and Ni), and the like, but are not limited thereto.

[0049] The positive electrode active material may have a coating layer. The coating layer is a layer containing a substance that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.

[0050] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).

[0051] For the solid electrolyte, the conductive assistant, and the binder, reference can be made to the above descriptions regarding the electrode mixture of the present disclosure.

[0052] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode active material layer (mass of positive electrode active material: mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 50:50.

[0053] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.

[0054] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, etc., and these metals plated or vapor-deposited with nickel, chromium, carbon, etc. may be used, but is not limited to these.

[0055] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred. EXAMPLES

[0056] Example 1 Synthesis of Silicon Clathrate Electrode Active Material Particles (Porous) Si powder (Kojundo Kagaku, SIEPB32) was prepared as a silicon (Si) source. Metallic lithium (Li) and this Si powder were weighed out so that the molar ratio of Li:Si was 4:1. The weighed Li and Si powder were mixed and reacted in a mortar under argon atmosphere at room temperature for 0.5 hours to obtain lithium silicon (Li4Si). The obtained Li4Si was reacted with ethanol in an argon atmosphere. Furthermore, the reaction product was washed with a 3 wt% hydrogen fluoride (HF) solution, filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain Si powder with a porous structure.

[0057] (alloying) A sodium silicon (NaSi) alloy was produced using Si powder having a porous structure and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. NaH and Si powder having a porous structure were weighed out so that the molar ratio was 1.05:1, and the weighed NaH and Si powder having a porous structure were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.

[0058] (Clatification) The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed to a molar ratio of 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel and heated in a heating furnace under an argon atmosphere at 345°C for 40 hours to react, thereby obtaining a silicon clathrate. The obtained silicon clathrate was acid-washed using a mixed solvent of HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain silicon clathrate electrode active material particles having a porous structure.

[0059] Example 2 The same procedure as in Example 1 was repeated except that the clathrate was heated at 345°C for 60 hours, and that after acid washing, filtration, and drying, the product was further washed with a 3 wt% HF solution, filtered, and then dried at 120°C for 3 hours or more. Thus, silicon clathrate electrode active material particles having a porous structure were obtained.

[0060] Example 3 Silicon clathrate electrode active material particles having a porous structure were obtained in the same manner as in Example 2, except that the clathrate was heated at 335° C. for 60 hours.

[0061] Example 4 Silicon clathrate electrode active material particles having a porous structure were obtained in the same manner as in Example 2, except that the clathrate was heated at 325° C. for 60 hours.

[0062] Example 5 Silicon clathrate electrode active material particles having a porous structure were obtained in the same manner as in Example 2, except that the clathrate was heated at 345° C. for 40 hours.

[0063] Example 6 Silicon clathrate electrode active material particles having a porous structure were obtained in the same manner as in Example 2, except that the clathrate was heated at 345° C. for 20 hours.

[0064] Example 7 (alloying) A sodium silicon (NaSi) alloy was produced using Si powder (Kojundo Kagaku, SIEPB32) and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. NaH and porous Si powder were weighed out to a molar ratio of 1.05:1, and the weighed NaH and Si powder were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.

[0065] (Clatification) The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed to a molar ratio of 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel and reacted in a heating furnace under an argon atmosphere at 345°C for 40 hours to obtain a silicon clathrate. The obtained silicon clathrate was acid washed using a mixed solvent of HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the filtered solid was dried at 120°C for 3 hours or more. Furthermore, the obtained silicon clathrate was washed with a 3wt% HF solution, filtered, and then dried at 120°C for 3 hours or more to obtain silicon clathrate particles.

[0066] (Porous) Li and the obtained silicon clathrate particles were weighed out so that the molar ratio was 2.5:1. The weighed Li and Si powders were mixed and reacted in a mortar under an argon atmosphere at room temperature for 0.5 hours to obtain lithium silicon (Li 2.5 The obtained Li 2.5Silicon was reacted with ethanol in an argon atmosphere to obtain silicon clathrate electrode active material particles having a porous structure.

[0067] Comparative Example 1 Silicon clathrate electrode active material particles of Comparative Example 1 were obtained in the same manner as in Example 2, except that in the alloying, Si powder (Kojundo Kagaku, SIEPB32) was used instead of Si powder having a porous structure.

[0068] The surface of the electrode active material particles in each of the above examples may contain a coating or impurities containing O, C, N, or the like.

[0069] (Making a lithium-ion battery) (Preparation of negative electrode mixture) Butyl butyrate, a 5 wt% butyl butyrate solution of polyvinylidene fluoride (PVDF) binder, vapor grown carbon fiber (VGCF) as a conductive additive, electrode active material particles of each example, and Li2S-P2S5 glass ceramic as a sulfide solid electrolyte were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to obtain a slurry-like negative electrode mixture (negative electrode mixture slurry).

[0070] (Formation of negative electrode active material layer) The obtained negative electrode composite slurry was applied onto a copper (Cu) foil serving as a negative electrode current collector layer by the blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C to form a negative electrode active material layer on the negative electrode current collector layer.

[0071] (Formation of solid electrolyte layer) Heptane, a 5 wt% heptane solution of butylene rubber (BR)-based binder, and Li2SP2S5-based glass ceramic as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) to obtain a solid electrolyte slurry.

[0072] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet by a blade method using an applicator, and dried for 30 minutes on a hot plate heated to 100°C to form a solid electrolyte layer. Multiple solid electrolyte layers were produced.

[0073] (Preparation of Positive Electrode Mixture) A polypropylene container is filled with butyl butyrate, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi with an average particle size of 6 μm as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5-based glass ceramic as a sulfide solid electrolyte, and VGCF as a conductive additive were added to the container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with the ultrasonic dispersion device, and shaken for 3 minutes with the shaker to obtain a slurry-like positive electrode mixture (positive electrode mixture slurry).

[0074] (Formation of Positive Electrode Active Material Layer) The obtained positive electrode mixture slurry was applied onto an Al foil serving as a positive electrode current collector layer by a blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a positive electrode active material layer on the positive electrode current collector layer.

[0075] (Battery Assembly) The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 100 kN / cm and a temperature of 165° C. to obtain a positive electrode laminate.

[0076] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 60 kN / cm and a temperature of 25° C. to obtain a negative electrode laminate.

[0077] Furthermore, the Al foil as a release sheet was peeled off from the surfaces of the solid electrolyte layers of the positive electrode laminate and the negative electrode laminate, and then the Al foil as a release sheet was peeled off from the third solid electrolyte layer.

[0078] The positive electrode laminate and the negative electrode laminate were laminated on top of each other so that the solid electrolyte layer side of each laminate faced the third solid electrolyte layer, and the laminate was set in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the laminate was set in a flat uniaxial press and pressed for 1 minute at a pressure of 200 MPa and a press temperature of 120° C. Thus, an all-solid-state battery was obtained.

[0079] "evaluation" <Oxygen ratio on the surface> The oxygen ratio on the surface of the electrode active material particles was calculated from the results of measurement by non-dispersive infrared absorption method using an oxygen / nitrogen / hydrogen analyzer (Horiba, Ltd., EMGA-930) after melting with oxygen gas.

[0080] <Specific surface area> The specific surface area of ​​the electrode active material particles was calculated by analyzing the surface area measured by a low-volume adsorption method (nitrogen gas adsorption method) using nitrogen gas by the BET method. For this analysis, BELSORP MAX II manufactured by MICROTRACBEL was used.

[0081] <Measurement of increase in confining pressure> The cell prepared using the restraining tool was restrained at a predetermined restraining pressure, and the increase in restraining pressure was measured when the cell was charged at a constant current and constant voltage up to 4.55 V at a 10-hour rate (1 / 10C). A large increase in the restraining pressure means that the active material has a large expansion amount. The increase in the restraining pressure is the difference between the maximum and minimum values ​​of the restraining pressure, and the values ​​of the examples are shown as relative values ​​when the value of Comparative Example 1 is set to 100.

[0082] "result" The surface oxygen ratio and specific surface area of ​​the electrode active material particles were measured, and the surface oxygen ratio (wt%) / specific surface area (m 2 / g) and the measurement results of the increase in confining pressure are shown in Table 1.

[0083] [Table 1]

[0084] As shown in Table 1, the ratio of surface oxygen (wt%) to specific surface area (m 2 The batteries of the examples including electrode active material particles having an average particle diameter (A / g) within the range of the present disclosure had a smaller increase in confining pressure than the batteries of the comparative examples.

Claims

1. Silicon clathrate electrode active material particles that satisfy the following relational formula: 0 < Surface oxygen ratio (wt%) / specific surface area (m 2 / g)<0.

3.

2. The electrode active material particles according to claim 1 , which satisfy the following relational formula: 0.05≦Oxygen ratio on the surface (wt%) / specific surface area (m 2 / g)≦0.

1.

3. The electrode active material particles according to claim 1 or 2, which have a porous structure.

4. An electrode mixture comprising the electrode active material particles according to claim 1 or 3.

5. An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to claim 4. Lithium-ion battery.

Citation Information

Patent Citations

  • Active material, negative electrode layer, battery and these manufacturing methods

    JP2021158003A